Optimal use of bendamustine in hematologic disorders: Treatment recommendations from an international consensus panel – an update. Issue 4 (2nd April 2016) - Cheson, Bruce D.; Brugger, Wolfram; Damaj, Gandhi; Dreyling, Martin; Kahl, Brad; Kimby, Eva; Ogura, Michinori; Weidmann, Eckhart; Wendtner, Clemens-Martin; Zinzani, Pier Luigi
Abstract: Bendamustine has achieved widespread international regulatory approval and is a standard agent for the treatment for chronic lymphocytic leukemia (CLL), indolent non-Hodgkin lymphoma and multiple myeloma. Since approval, the number of indications for bendamustine has expanded to include aggressive non-Hodgkin lymphoma and Hodgkin lymphoma and novel targeted therapies, based on new bendamustine regimens/combinations, are being developed against CLL and lymphomas. In 2010, an international panel of bendamustine experts met and published a set of recommendations on the safe and effective use of bendamustine in patients suffering from hematologic disorders. In 2014, this panel met again to update these recommendations since the clarification of issues including optimal dosing and management of bendamustine-related toxicities. The aim of this report is to communicate the latest consensus on the use of bendamustine, permitting the expansion of its safe and effective administration, particularly in new combination therapies.